2018 IEEE 12th International Conference on Semantic Computing (ICSC) 2018
DOI: 10.1109/icsc.2018.00059
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Batch Size on Stopping Active Learning for Text Classification

Abstract: When using active learning, smaller batch sizes are typically more efficient from a learning efficiency perspective. However, in practice due to speed and human annotator considerations, the use of larger batch sizes is necessary. While past work has shown that larger batch sizes decrease learning efficiency from a learning curve perspective, it remains an open question how batch size impacts methods for stopping active learning. We find that large batch sizes degrade the performance of a leading stopping meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Ong, Smola, and Willamson 2003) have identified that the machine learning performance is sensitive to the kernel width selection in similarity measurement. There has also been research (Beatty, Kochis, and Bloodgood 2018) studying the behavior of batch size in query selection for active learning. Therefore, given a limited number of labeled samples, it is critical to automatically determine a good set of hyperparameters for active learning in order to efficiently maximize the classification performance.…”
Section: Introductionmentioning
confidence: 99%
“…Ong, Smola, and Willamson 2003) have identified that the machine learning performance is sensitive to the kernel width selection in similarity measurement. There has also been research (Beatty, Kochis, and Bloodgood 2018) studying the behavior of batch size in query selection for active learning. Therefore, given a limited number of labeled samples, it is critical to automatically determine a good set of hyperparameters for active learning in order to efficiently maximize the classification performance.…”
Section: Introductionmentioning
confidence: 99%
“…Following previous work, we set w to three [13], [18]. As [33] advised, if a relatively large batch size is used, a smaller value for w should be used in order to mitigate the degradation in stopping method performance caused when using larger batch sizes. Table I shows the performance of unlabeled data stopping methods.…”
Section: Stopping Methods Parametersmentioning
confidence: 99%
“…Again, we see there is not much difference in performance of our forecasting system when we vary batch percent. It is possible that with much larger batch percents we would see a change in forecasting performance, but using larger batch percents is known to have various negative effects on active learning [38], [39], so we did not investigate the impact with larger batch percents that are less likely to be used in practice.…”
Section: A Impact Of Batch Percentmentioning
confidence: 99%